HUBUNGAN BODY IMAGE, ASOSIASI EMOSIONAL, DAN POLA KONSUMSI DENGAN STATUS ANEMIA PRAMUGARI - Khaulah Ali Badjree; Lailatul Muniroh (Media Gizi Indonesia, 2017)
A stewardess is one of the professions that pay attention to body shape and diet. A stewardess need enough nutrition to do their activities. Suxh as iron, folic acid, and vitamin B12 to prevent them from anemia. Consumption of these foods can be influenced by several things one of them is the presence or absence of emotional influence in the food selection. The purpose of this research was to analyze the relationship of body image, emotional association and consumption pattern with anemia status of stewardess. This study used a cross-sectional design. Sample size using rule of thumb and obtained 37 respondents. Relationship analysis on the variables in this study using chi-square, spearman correlation and pearson correlation. The results of this study showed that most stewardess having negative body image and emotional association who was emotionally affected. A stewardess who suffer from anemia as much 45.9%. This research showed that there was a relationship between body image (p=0.003) and emotional association (p=0.001)with anemia status of the stewardess, whereas the consumption patterns of Fe, folic acid, vitamin B12 (p=0.314) and inhibitors (p=0.921) didn’t correlate with anemic status of stewardess. The conclusion in this study is that most stewardess tend to have anemia if they have a negative body image and there is an emotional influence in the selection of food consumed in daily life. Suggestions that can be given so that stewardess can control their emotions in their dietary needs and also change the mindset of negative body image to be fi t for health.